ASPEK HUKUM PERBANKAN SYARIAH DAN IMPLEMENTASINYA DI INDONESIA - M Ali Mansyur (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Legal Aspects of Sharia Banking Legislation, Law Number 21 of 2008, in terms of judicial philosophy and Sociological basically a sense of Justice has addressed the needs of the Islamic Ummah as a consequence of legal pluralism live and grow in the dynamics of Indonesian society. While from the juridical formalistic approach through the legal umbrella Act No.3 of 2006 and Act No. 4 of 2004 its implementation requires a judge in creating and upholding justice, should know and understand the aspirations and values of living in society and orientation, which should put forward justice together with the orientation of legal certainty and expediency. Keywords: shariah banking, implementation